Using audio and video listening materials to improve ESL undergraduates' listening comprehension - Rashasoor, Heero Mohialdeen; Tan, Bee Hoon; Chan, Mei Yuit (Universiti Putra Malaysia Press, 2016)
Listening is an important language skill and should be acquired by all language learners. In training the listening skill, many online freeware and courseware can be applied, for example, Schoology. It can be used to entice students’ interest to do listening exercises online, and subsequently improve their listening competence. This study investigated the efficacy of two different modes of listening materials, audio and video, through a quasi-experiment. It also examined if Schoology was useful in improving ESL undergraduates’ listening skills through analyzing the participants’ perception to its use. The study was conducted in a public university in Malaysia. The participants were 50 undergraduates assigned to two experimental groups. The measurement instruments comprised a pre-test, a post-test, and a questionnaire. The two groups received a series of treatment in the form of parallel listening materials in either audio or video mode administered through Schoology. The results showed that the audio mode achieved a higher mean than the video mode in the post-test. In addition, the study found that the listening exercises conducted through Schoology produced a significant gain. Outcomes from this study should be beneficial in facilitating language teachers and policy makers to choose the right mode of listening materials for the language classrooms.